About reliable indicator of proprioception in agility control - Zaporozhanov V.A (Kharkov National Pedagogical University, 2013)
Agility is seen as a complex physical quality due to a complex interaction of motor, visual, auditory, vestibular analyzers. A special role in this development is given to kinesthesia. This motor feeling largely determines the accuracy of the differentiation of power, temporal and spatial characteristics of voluntary movement and is regarded as one of the main indicators of quality in the structure of human mobility. The purpose of the study - to make a proposal to improve the procedures for monitoring mobility by quantifying the state of kinesthesia exercise. Material and methods. The study included 101 soccers at the age of 14-18 years. Measured fidelity 50% of the maximum values of the force in the joints of upper and lower extremities seven times. Reliability measurement was evaluated by calculating the linear correlation between the results in the sequential series. Stability measurements evaluated in the same way between the results of precision in the first and seventh attempt. Results . Among the surveyed found significant individual differences in the state of kinesthesia joint efforts in terms of accuracy. Also, different abilities learning accuracy differentiation efforts in a series of successive measurements. Conclusions . The expediency of improving the control of mobility in the direction of study of quantitative and qualitative assessment of kinesthesia in the specific conditions of physical education.